The Application of Chatbot for Customer Service in E-Commerce - Billy Wibowo; Helen Clarissa; Derwin Suhartono (Engineering, MAthematics and Computer Science (EMACS) Journal, 2020)
The use of intelligent machines such as chatbot have been increasing each day. The main idea that we wanted to address in our paper is that with the capabilities that intelligent machines have it will be able to replace humans in doing a certain task and be able to bring better advantages in the long run. The focus of this study is that we are able to manipulate the ability of chatbot to impersonate how humans interact with each other and will enable it to play a role as to handle the customer service in e-commerce websites or applications which will be an alternative to replace the traditional customer service